The thermodynamics of solutions and binary liquid mixtures - Mercer-Chalmers, June Dawn (Rhodes University, Faculty of Science, Department of Chemistry, 1993)
The thesis is presented in two parts. In part one, the excess thermodynamic properties have been determined for several binary liquid mixtures, with the aim of testing theories of liquid mixtures. The excess molar enthalpies, Hem, have been determined using an LKB flow microcalorimeter, and the excess molar volumes, Vem, have been determined using an Anton Paar densitometer. The HemS and VemS have been measured at 298.15 K for binary systems involving an alkanol (methanol, ethanol, I-propanol, 2-propanol) mixed with a hydrocarbon (l-hexene, I-heptene, l-octene, I-hexyne, I-heptyne, l-octyne, toluene, mesitylene, 0-, m-, or p-xylene, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclodecane). The results show trends relating to the degree of unsaturation, or size, of component molecules as well as the position of the hydroxyl group on the alkanol. Measurements were also made on mixtures involving an (n-alkane + a pseudo-n-alkane) and ( a cYcloalkane + a pseudo-cycloalkane). Two theories of liquid mixtures were tested in this work. The first theory tested was the theory of Congruency. This theory was tested, by means of a null test, on a novel set of mixtures involving an n-alkane (hexane, heptane, octane, decane, dodecane) + a pseudo-nalkane,and mixtures of a cycloalkane (cyclopentane, cyclohexane, cycloheptane, cyclooctane)+ a pseudo-cycloalkane. Deviations from the theory was less than the experimental error for the (n-alkane + pseudo-n-alkane) mixtures. However, significant deviations were observed for the mixtures of (a cycloalkane + a pseudo-cycloalkane). The second theory tested was the Flory theory, which has been used to predict the excess molar enthalpies and excess molar volumes for the mixtures involving (a 1-alkene, or 1-alkyne, or methyl-substituted benzene) + an alkanol. The results show that the theory does not hold for hydrocarbon mixtures involving an alkanol. In the second part of this thesis, the partial molar volumes, at infinite dilution, of binary solution involving a solid solute (18-crown-6 ether, dibenzo-18-crown-6 ether, dicyclohexanov 18-crown-6 ether, 15-crown-5 ether, or cryptand-222) are determined in various solvents. The results were repeated with a view to determine the volume changes at infinite dilution upon complexation, ΔV∞ of the crown ether or cryptand with a metal halide salt, MX (NaCl, NaI, KCl, KI, CsCl, CsI). The ΔV∞ results were compared with results in the literature for cryptand-222 (c-222) and dibenzo-18-crown-6 ether (B₂CE6) complexed with MX, and the study was extended to include further MX complexes with c-222 and B₂CE6, as well as MX complexes with 15-crown-5 ether and dicyclohexano-18-crown-6 ether. ΔV∞ results were correlated with the Hepler prediction of the electrostriction solvent effect.
Keywords: Thermodynamics; Liquids; Solution (Chemistry)